PERAN GREENPEACE DALAM PENANGANAN KERUSAKAN LINGKUNGAN (POLUSI UDARA DAN AIR) DI CHINA - Dori Gusman; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to determine about Greenpeace role in the Handing ofEnvironmental Damages(Study Case Water Pollution and Air Pollution InChina).Type of this research is descriptive analysis. China’s environmentpollution issue came up when the growth of China’s economy andindustrialization shows the great development. By the positive development, theeffect of progress of China’s economy and industrialization brings bad impactagainst environment sector.The writer try to describe and explain aboutGreenpeace role in resolving water and airpollution which occurred at China.Sources to be presented in this research is secondary sources.Sources were obtained through literature review, other books, internet, ect. Thesources analysis isqualitative analysis.This research uses a level analysis ofinternational organizations, use perspective that describes the state of pluralismis not the only rational actors in international relations. Uses non states actors,using the theory that describes the role of guidance that is given structurally.The conclusions of this research the role that is carried out by Greenpeace inaddressing air and pollution problems in China. Delivering results that affectthelevels of pollution in China, then showed the presence of Greenpeace’s interestindication in China.Keywords : Greenpeace, role, environmental damages, air and water pollutionin China.